Apakah Corporate Governance dan Kinerja Perusahaan meningkatkan Kualitas Sustainability Reporting? - Retnaningrum, Pembayun Kinanti; Alexander, Nico (Media Bisnis, 2024)
The operational activities of the company have the objective of maximizing profits. Every profit made will come at a cost of the social and environmental circumstances. The continual existence of humans and other living things associated with the company's operations will be impacted by this issue. Due to their need to survive, businesses are now more concerned with the environment and its surroundings, as shown by the CSR that they report on in their sustainability reports. The performance of the company and the presence of good corporate governance both support this disclosure. The purpose of this study was to gather empirical data regarding the impact of corporate performance and governance on sustainability report disclosure. The companies that are used are those that publish sustainability reports between 2020 and 2022 and are classified as basic material, cyclical, and non-cyclical companies. Purposive sampling was used to choose the research sample, which included 37 companies in total. Regression analysis on panel data was utilized to test the research hypothesis. The findings show that while leverage has a negative impact on disclosure in sustainability reports, governance, liquidity, and profitability have no effect on disclosure. Stakeholders can learn from this study what elements may improve the disclosure of information in corporate sustainability reports.